Methodology for assigning ESG ratings - D. V. Zhatikova; P. S. Scherbachenko (Вестник университета)
The article presents study results of methodologies for assigning indices and ESG rating, ESG ranking by the largest Russian rating agencies: Analytical Credit Rating Agency, National Rating Agency, Expert RA JSC, and the Russian Union of Industrialists and Entrepreneurs. Growth of negative impact on the environment and aggravation of social and corporate problems have been outlined as relevance reasons of the issue. Theoretical bases of three key blocks (ecology (E), society (S), corporate governance (G)) have been stated. Known rating scales for assessing the level of sustainable development of Russian enterprises have been analyzed and distinctive features found. The influence of a company’s position in the sustainable development rating on construction of long-term trusting relations of the organization with investors, counterparties, consumers, staff, mass media, and expert community, as well as public authorities has been emphasized. As a result of the research work the authors have proposed their own methodology for assigning ESG ratings that can serve as a basis for generalizing all the technologies available in the market to assess companies’ compliance with the ESG agenda.